Ukraine - Lerner Publications Company. Geography Dept. (Minneapolis : Lerner Publications, 1993)
Examines the history, geography, ethnic mixture, politics, economy, and future of the former Soviet republic of the Ukraine.
The land and people of Ukraine -- Ukraine's story -- Making a living in Ukraine -- What's next for Ukraine?
Includes index and glossary.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.3
4-6
Keywords: Ukraine -- Juvenile literature; Ukraine; Ukraine